Sheathless and fluoroscopy-free retrograde intrarenal surgery: a single center experience - Ramesh, M. Lakshmi; Yuvaraju, Y.; Theja, Bathalapalli Ravi; Jagirdar, Sayyed Faisal; Gaddam, Yaswanth; Eswar, Pinnamaneni Sumanth (International Journal of Research in Medical Sciences, 2025)
Background: This study was done to evaluate the effectiveness and safety of minimally invasive approach to treating renal stones using sheathless and fluoroscopy-free flexible ureterorenoscopic laser lithotripsy (FURSL). Methods: A prospective study was conducted on 270 patients who underwent FURSL between January 2023 and March 2024. The procedure involved a semi-rigid ureteroscopic assessment with 6 and 8 Fr ureteroscope. A 7.5 Fr flexible URS was inserted into the PCS by side of guidewire sheathless and fluoroscopy-free, followed by the use of a holmium laser to fragment and dust stones in situ. Results: The study population consisted of 270 patients including 170 males (62.96%) and 100 females (37.04%) with a mean age of 40.65 years (range: 3-70 years) were evaluated. The mean stone size was 17.23 mm (range: 8-41 mm). Complete stone-free status was achieved in 244 (90.37%) patients and clinically insignificant residual fragments (CIRF) in 4 (1.48%), while residual stones were still present in 22 (8.15%) patients. Postoperative complications occurred in 46 (17.4%) cases and were mostly minor, including fever in 34 (12.6%), pyelonephritis in 8 (3.0%), subcapsular hematoma in 2 (0.7%) and steinstrasse in 2 (0.7%). These complications were Clavien I-II, GI in 34 (12.6%) patients, GII in 10 (3.7%), and Clavien IIIb in 02 (0.7%). No major complications were observed. Stone size ≥2 cm, operative time ≥30 minutes, and lasing time ≥20 minutes were significantly associated with a higher rate of complications and lower stone-free rates (p<0.05). Conclusions: Sheathless and fluoroscopy-free FURSL are effective and safe for renal stone management, especially for stones under 2 cm in diameter. This process is a feasible option for avoiding sheath complications, which can protect surgeons from the negative effects of radiation.